Analisis Dampak Serangan Wormhole terhadap Protokol Routing Ad-Hoc On Demand Distance Vector (AODV) pada LoRa - Muhamad Ralfi Akbar; Dany Primanita Kartikasari; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Long Range (LoRa) is one of IoT technology used in a system that require long distance communication and in a need of low cost system. Delivering a packet on LoRa takes time depending on the distance to the destination, the farther the distance, the longer delivery time will take. This makes LoRa network security while delivering packet, vulnerable to attacks. This research analyze packet delivery on LoRa using the AODV routing protocol and the impact of Wormhole attack lon the AODV routing protocol on LoRa. This study uses 3 LoRa nodes and 1 malicous wormhole node. The analysis is reviewed with QoS paramers, namely Troughput, Delay, Jitter, and Packet Loss. The result of the test show that Wormhole attack affects the performance of packet delivery in LoRa. In the non-attack scenario, the average Delay value is 0.171s, Packet Loss is 0%, the average of Troughput is 408,321 kbps, and the average of Jitter is 0.0003ms. In the Wormhole attack scenario, the average Delay values is increased to 0.343s, Packet Loss increased to 70%, Troughput decreases by an average of 204,105 kbps and Jitter increases by an average of 0.05724ms. It can be concluded that Wormhole attack on the AODV routing protocol affects the qualiy of QoS on the delivery of each packet.